The Parents' Efforts To Overcome Gadget Use Addiction in Early Childhood - Ani Aryati; Idmar wijaya; Ari Pratama; Eka Yanuarti (AL-ISHLAH: Jurnal Pendidikan, 2023)
Currently, gadget users have penetrated the world of children who still have limited knowledge, namely early childhood. Early childhood is the best imitator. So that, when the child gets a good stimulus, the child will be good, but if the child gets a bad stimulus, it will interfere with the child's development process. The aims of this study were: 1) to determine the effect of gadget addiction on children's development; 2) to find out the effects of gadget addiction on children; 3) to find out the efforts of parents in dealing with children who are addicted to gadgets. The research method used is a type of qualitative research that comes from primary data and secondary data. Data collection techniques are carried out through observation, interviews, and documentation to obtain data/information related to research problems. This research was conducted in Suak Batang Village, Gandus District, Palembang City, for parents and early childhood with a sample of 10% of the population in Suak Batang Village, namely 37 people. The conclusions of this study are 1) that gadget addiction causes children to like to spend time at home playing with gadgets and, in early childhood, watching violent content, thus influencing children to be arrogant when playing with their friends. 2) That gadget addiction in children has a positive impact, such as increasing knowledge, developing imagination, facilitating communication, and training children's creativity. But there are also negative impacts, such as sleep disorders, health, and development, which can also affect children's behavior, namely; restlessness, aloofness, lack of concentration, and laziness. 3) that the efforts of parents in overcoming gadget addiction in children are mentoring children, limiting the use of gadgets, scheduling gadget use, not giving children full access to gadget use.